2014
DOI: 10.1186/1423-0127-21-46
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia-induced protein phosphatase 2A activation reduces PC12 cell proliferation and differentiation

Abstract: BackgroundIntermittent hypoxia (IH) plays a critical role in sleep breathing disorder-associated hippocampus impairments, including neurocognitive deficits, irreversible memory and learning impairments. IH-induced neuronal injury in the hippocampus may result from reduced precursor cell proliferation and the relative numbers of postmitotic differentiated neurons. However, the mechanisms underlying IH-induced reactive oxygen species (ROS) generation effects on cell proliferation and neuronal differentiation rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
4
13
0
Order By: Relevance
“…Liu et al (2009) reported that hypoxia-induced apoptosis is related to p38MAPK activity in cultured rat cerebellar neurons. However, MAPK members can be activated by ROS products generated intracellularly, as well as by an exterior substance, such as H 2 O 2 administered (Banno et al, 2001;Gaitanaki et al, 2007;Chen et al, 2009Chen et al, , 2014. Our findings are consistent with those of the previous studies mentioned above and comparable with the recent evidence that the members of different proteins such as ERK1/2, p38MAPK, and MAPKs mediate neuronal apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Liu et al (2009) reported that hypoxia-induced apoptosis is related to p38MAPK activity in cultured rat cerebellar neurons. However, MAPK members can be activated by ROS products generated intracellularly, as well as by an exterior substance, such as H 2 O 2 administered (Banno et al, 2001;Gaitanaki et al, 2007;Chen et al, 2009Chen et al, , 2014. Our findings are consistent with those of the previous studies mentioned above and comparable with the recent evidence that the members of different proteins such as ERK1/2, p38MAPK, and MAPKs mediate neuronal apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…These experiments allow us to conclude that the hyper-accumulation of O 2 - in det2-9 did not involve the NADPH oxidase pathway. So attention was focused on the peroxidase pathway [ 29 ], by treating seedlings with either salicylhydroxamic acid (SHAM) [ 42 ] or 1,10-phenanthroline (1,10-Phe) [ 43 ], inhibitors of peroxidase activity. The root length of det2-9 was significantly increased by both treatments, whereas root growth of WT was slightly inhibited ( S11A and S11B Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it was still unclear whether CIH could increase or decrease neuronal proliferation. [ 39 40 ] Few EdU positive neurons were observed in all study groups [ Figure 3 ]. This implied that CIH and LiCl did not affect the hippocampal neuronal proliferation.…”
Section: Discussionmentioning
confidence: 99%